Dr. Guy Cappuccino — Deep Plane Facelift — Mount Airy - Cappuccino, Guy (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Guy Cappuccino, practicing in Mount Airy, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003274; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; mount airy